Electric and mechanical properties of Pb(Fe$_{0.5}$Nb$_{0.5}$)O$_{3}$ ferroelectric ceramics - Zachariasz, Radosław; Ilczuk, Jan (Archives of Acoustics, 2007)
In this work we report the synthesis of the Pb(Fe$_{0.5}$Nb$_{0.5}$)O$_{3}$ (PFN) powders and sinteredceramics. The ceramics were prepared from oxides: Fe$_2$O$_3$, Nb$_2$O$_5$ and PbO by two-stagecolumbite method by calcination. PFN powders were dried and formed in samples in shapeof discs (10$×$1) mm$^3$ and rectangular bars (26$×$10$×$1) mm$^3$. The samples were sinteredby conventional ceramic sintering (CCS) method at temperature of 1323 K for 2 h in air. Thedensity of the ceramic samples was determined to be $ρ = 8200$ kg/m$^3$. The obtained resultsof investigations of electric and mechanical properties such as: Young’s modulus $E$, electricpermittivity $ε$ and tangent of dielectric loss of angle tan $δ$ of the Pb(Fe$_{0.5}$Nb$_{0.5}$)O$_3$ ceramicsobtained are presented.